Inter-Grade Text Readability Variation of English Course Books in Ghana: A Review of Selected Pre-Tertiary English Course Books - Justine Bakuuro; Joseph Ajogwu Onoja (Edulitics (Education, Literature, and Linguistics) Journal, 2024)
This study investigates whether the content of textbooks for senior high school English students in Ghana are appropriate for the students that are supposed to read them. This will tell you how much readability differs between grades. Data was sourced from Global Series which is an English course book used in Ghana. According to the study’s results, derived from a descriptive research protocol and the constructivist research paradigm, there is considerable random theft of words in Ghanaian English textbooks from the readers who are supposed to read them. That’s because the readability scores of sampled texts were actually much higher than the grades the students were supposed to receive. The literature was focused on high-school students but despite that, the majority of texts proved to be readerable for undergraduate and postgraduate students. That was because the works had very high readability coefficients, and were therefore, as Flesch’s translated index showed, illegible. The inter-grade readability gap was a bit too large as well which is far higher than the acceptable inter-grade rates recommended by Halliday and Gunning (33.3% vs 35% respectively) which were referenced in the methodology literature used in this study. Therefore, before assigning works to the levels of study, this article recommends a systematic check that they can be applied to all grades.